The relationship between menstrual cycle and psychological stress on acne vulgaris incidence - Ania K P Dewi; Rina Munirah B; Westinawati Rahman H (ACTA Medical Health Sciences, 2024)
Acne vulgaris (AV) is a chronic inflammation of the pilosebaceous unit and presents with a polymorphic clinical picture such as comedones, papules, pustules, nodules, and scars. AV is often experienced by both women and men, affecting 85% of young adults aged 12-25 years, with women more commonly affected than men. There are several triggers that contribute to the onset of AV, including the menstrual cycle and psychological stress. This study aims to determine the relationship between the menstrual cycle, psychological stress, and the occurrence of acne vulgaris in female medical students at Universitas Jenderal Achmad Yani. The research design uses a cross-sectional study approach. There were 48 people who met the inclusion criteria. Respondents in this study were asked to fill out informed consent forms, questionnaires, and indicate their availability for standardized facial photos. The results of this study obtained a p-value of 1.000 and 0.529 (p-value > 0.05). It was found that there is no statistically significant association observed between either regular menstrual cycles or severe psychological stress and the presence of acne vulgaris in this sample. The odds ratios for both variables (1.052 and 1.303) suggest minor increases in the odds of acne vulgaris presence, but they do not reach statistical significance. This relates to the occurrence of acne vulgaris, which is not only caused by factors such as the menstrual cycle and psychological stress but also by various triggering factors including diet, use of cosmetics, facial hygiene, and unhealthy sleep patterns. DOI : 10.35990/amhs.v3n1.p51-59 REFERENCES Li D, Chen Q, Liu Y, Tang W, Li S. The Prevalence of Acne in Mainland China: a systematic review and meta-analysis. BMJ Open. 2017;7(8). Agesti D, Astuti S, Mustika A. Penanganan Jerawat Sindrom Akumulasi Dahak Menggunakan Akupunktur dan Herbal Jianghuang. J Vocational Health Studies. 2020;4:15–20. Jusuf NK, Putra IB, Sutrisno AR. Correlation Between Stress Scale and Serum Substance P Level in Acne Vulgaris. Int J Gen Med. 2021;14:681–686. Heng AH, Chew F. Systematic Review of the Epidemiology of Acne Vulgaris. Scientific Reports. 2020;10:5754. Sutaria AH, Masood S, Saleh HM, Schlessinger J. Acne Vulgaris. In: StatPearls [Internet]. Treasure Island (FL): StatPearls Publishing; 2023 Aug 6. Available from: https://www.ncbi.nlm.nih.gov/books/NBK459173/ Fadilah AA. Stres Psikologis Terhadap Timbulnya Akne Vulgaris. J Ilmu Kesehatan Sandi Husada. 2021;10:390–391. Wijayanti N, Diana ED, Irawanto ME. Hubungan Tingkat Stres dengan Derajat Keparahan Akne. Health Med J. 2023;5:39–43. Sirajudin A, Sibero HT, Anggraini DI. Prevalensi dan Gambaran Epidemiologi Akne Vulgaris di Provinsi Lampung. JK Unila. 2019;3:308–312. Lestari RT, Gifanda LZ, Kurniasari EL, Harwiningrum RP, Kelana AP, Fauziyah K, et al. Perilaku Mahasiswa Terkait Cara Mengatasi Jerawat. J Farm Komunitas. 2021;8:15–19. Hartono LM, Kapantow MG, Kairupan TS. Pengaruh Menstruasi terhadap Akne Vulgaris. E-CliniC. 2021;9:305–310. Prayuni ED, Imandiri A, Adianti M. Terapi Menstruasi Tidak Teratur dengan Akupunktur dan Herbal Pegagan (Centella asiatica L.). J Vocational Health Studies. 2018;2:86–91. Yadnya KS, Wiraguna AA, Karna NP, Sudarsa PS. Hubungan Stres Terhadap Timbulnya Akne Vulgaris pada Mahasiswa Fakultas Kedokteran Universitas Udayana Program Studi Pendidikan Dokter Angkatan 2017. J Medika Udayana. 2020;9:66–67. Basri M, Usman J, Islamiah N. Hubungan Stres dengan Kejadian Acne Vulgaris pada Mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Makassar. J Komunitas Kesehatan Masyarakat. 2021;3:75–82. Musabiq SA, Karimah I. Gambaran Stres dan Dampaknya Pada Mahasiswa. InSight. 2018;20:74–79. Najmi FA, Ichlas I, Noneng E. Gambaran Tingkat Stres pada Mahasiswa Tahun Pertama Fakultas Kedokteran Universitas Jenderal Achmad Yani Angkatan 2016. Available from: https://doi.org/10.5281/zenodo Al-Falah AA, Subagio, Gading PW. Hubungan Pengetahuan dengan Tingkat Keparahan Jerawat (Acne Vulgaris) pada Mahasiswa Program Studi Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi. JOMS. 2021;2:11. Aziz T, Suryanti, Ramanda W. Faktor-Faktor yang Berhubungan dengan Timbulnya Acne Vulgaris pada Mahasiswi Angkatan 2021 Fakultas Kedokteran Universitas Batam. Zona Kedokteran. 2022;12:60. Roxanne J, Indira IG, Adiguna MS, Karmila IG. Proporsi dan Karakteristik Akne Vulgaris pada Mahasiswa Program Studi Sarjana Kedokteran dan Profesi Dokter Fakultas Kedokteran Universitas Udayana Tahun 2019. J Medika Udayana. 2021;10:91–97. Dewi AKP, et al. (Incomplete data, please review for clarification) Teresa A. Akne Vulgaris Dewasa: Etiologi, Patogenesis, dan Tatalaksana Terkini. J Kedokteran. 2020;8:953–960. Sihombing KA, Chalil MJ, Akbar A, Suryani D. Hubungan Tingkat Stres dengan Gangguan Siklus Menstruasi dan Dismenore pada Mahasiswi Fakultas Kedokteran Universitas Muhammadiyah Sumatera Utara Selama Masa Pandemi COVID-19. J Implementa Husada. 2023;4:22. Kementerian Kesehatan Republik Indonesia. Pedoman Pencegahan dan Penanggulangan Anemia pada Remaja Putri dan Wanita Usia Subur (WUS). Jakarta: Kemenkes; 2016. Larasati NA. Hubungan Tingkat Stres dengan Keteraturan Siklus Menstruasi pada Remaja. J Riset Kesehatan Masyarakat. 2023:72–79. Hediaty S, Herlambang, Shafira NN. Gambaran Tingkat Stres Mahasiswa Kedokteran Berdasarkan Medical Student Stressor Questionnaire di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi. JOMS. 2022;2:64. Sajuni, Agus. Stress Analytics of Medical Students at Faculty of Medicine University of Surabaya. JPKI. 2022;11:319–325. Na’im Q, Meher C. Hubungan Derajat Stres dengan Tingkat Keparahan Acne Vulgaris pada Mahasiswa Fakultas Kedokteran Universitas Islam Sumatera Utara Angkatan 2017. Ibnu Sina: J Kedokteran dan Kesehatan FK UISU. 2022;21:20–24.